Biodiversity in Marine Ecosystems—European Developments toward Robust Assessments - Heiskanen, Anna-Stiina; Berg, Torsten; Uusitalo, Laura; Teixeira, Heliana; Bruhn, Annette; Krause-Jensen, Dorte; Lynam, Christopher P.; Rossberg, Axel G.; Korpinen, Samuli; Uyarra, Maria C.; Borja, Angel (Frontiers in Marine Science, 2016)
Sustainability of marine ecosystems and their services are dependent on marine biodiversity, which is threatened worldwide. Biodiversity protection is a major target of the EU Marine Strategy Framework Directive, requiring assessment of the status of biodiversity on the level of species, habitats, and ecosystems including genetic diversity and the role of biodiversity in food web functioning and structure. This paper provides a summary of the development of new indicators and refinement of existing ones in order to address some of the observed gaps in indicator availability for marine biodiversity assessments considering genetic, species, habitat, and ecosystem levels. Promising new indicators are available addressing genetic diversity of microbial and benthic communities. Novel indicators to assess biodiversity and food webs associated with habitats formed by keystone species (such as macroalgae) as well as to map benthic habitats (such as biogenic reefs) using high resolution habitat characterization were developed. We also discuss the advances made on indicators for detecting impacts of non-native invasive species and assessing the structure and functioning of marine food-webs. The latter are based on indicators showing the effects of fishing on trophic level and size distribution of fish and elasmobranch communities well as phytoplankton and zooplankton community structure as food web indicators. New and refined indicators are ranked based on quality criteria). Their applicability for various EU and global biodiversity assessments and the need for further development of new indicators and refinement of the existing ones is discussed.